Pemanfaatan Produk Samping Pengolahan Minyak Kelapa Mandar (Blondo) di Desa Galung Lombok - Al Islamiyah, Syahmidarni; Tiffany, Margaretha Hanna; Indrastuti, Indrastuti (LPPM Universitas Trunojoyo Madura, 2023)
Blondo is a by-product of coconut oil processing that has not been optimally utilized among the community. The problem faced is that the residents of Galung Lombok Village do not have the knowledge and skills to use blondo. This community service aims to share knowledge as well as equip the ability to use blondo into blondo flour and its application in making cookies. Methods in this activity include material presentation and training. The results obtained in this service activity include: 1) blondo, a by-product of coconut oil processing, mandar is used in processed products, 2) participants have knowledge and skills in making blondo flour and applying it in making cookies. The conclusion of this activity is that people who participated in this service activity gained knowledge and skills to use blondo into blondo flour and cookies. The recommendation for this activity to be carried out continuously is the implementation of special assistance from the government to develop it into an economic activity for the people of Galung Lombok Village.